INFLUENCE OF THE IMPACT OF A RIGID ROD IN COFFEE MECHANICAL HARVESTING BY MECHANICAL VIBRATION - Gomes, Ely Queiroz; Santos, Fábio Lúcio; Mendes de Jesus, Valquíria Aparecida (Agrarian, 2017)
Nowadays, the coffee sector has passed by a transition due the lack of labor, which makes manual harvesting impracticable. The mechanization has been the solution found by the coffee farmers to overcome the problem of lack of labor and also reduce the production costs. The principle used to perform coffee mechanical harvesting is based on mechanical vibrations. The aim of this study was to evaluate the detachment efficiency behavior of the coffee fruits under mechanical vibrations transmitted to the fruit-stem system by impact of a rigid rod, and mechanical vibrations transmitted to the system without the impact. Trials to evaluate the fruits detachment were performed varying the vibration frequency, the ripening stage of the fruits, the number of fruits at the same stem and the way of transmission of the mechanical vibrations to the fruit-stem system. The detachment efficiency of red fruits was higher than green fruits. It was observed an increase of the detachment efficiency associated to the increase the frequency of vibration. Detachment efficiency obtained from mechanical vibrations transmitted due the impact of a rigid rod on fruit-stem system was 19.4% higher than mechanical vibrations transmitted without impact.